SELF-EFFICACY KELUARGA BERKORELASI DENGAN KESIAPAN MERAWAT ANGGOTA KELUARGA PASCA BEDAH ORTHOPEDI DI RUMAH SAKIT UMUM DAERAH MEURAXA BANDA ACEH - Rania Atika Putri; Meutia Yusuf; Sofyan Sufri; Ainal Mardhiah; Liwaul Hamdi; Wirda Hayati (Poltekkes Kemenkes Aceh, 2022)
Self-efficacy has 3 dimensions that are closely related to readiness to care, namely the dimensions of magnitude (difficulty), dimensions of generality (expectations), and dimensions of strength (strength). The purpose of this study was to determine the relationship between family self-efficacy and readiness to care for family members after orthopedic surgery at Meuraxa Hospital, Banda Aceh. This type of research uses a descriptive correlation design with a cross sectional approach. This study uses the Chi-Square correlation method with = 0.05. The study was conducted by distributing questionnaires to the patient's family. The results of this study indicate the P-value = 0.000 < = 0.05, meaning that there is a significant relationship between family self-efficacy and readiness to care for family members after orthopedic surgery in the Al-Bayyan Room, Raudah and Orthopedic Poly Hospital Meuraxa Banda Aceh. Based on the results of the study, it can be said that if the self-efficacy of the patient's family is high, it will make the family ready to care for or the higher the self-efficacy, the more readiness of the family to care for. This research is expected to be useful for post-surgical patients, health workers, hospitals and educational institutions in order to improve evaluation.